Ventajas obstétricas y perineales del parto vertical versus parto supino - Zurita Peña, Mishell Katherine (Machala : Universidad Técnica de Machala, 2020)
INTRODUCTION: Since ancient times, for the birth of their children, women adopted vertical positions that were prevailing for a long time. Upright positions benefit women in labor by allowing spontaneous pushing with more efficient contractions. OBJECTIVE: To determine the obstetric and perineal advantages of vertical delivery versus supine delivery. METHODOLOGY: A scientific literature review was carried out on the advantage of vertical delivery over horizontal delivery, in databases such as: EBSCO, SCIELO, PUBMED, from August 2015 to the present. DEVELOPMENT: In the systematic review and meta-analysis carried out by Zang et al, it was concluded that the upright position can reduce the incidence of surgical delivery, instrumental vaginal delivery, cesarean section, episiotomy, severe perineal trauma, severe pain and shortens the duration of the active pushing in the second stage of labor. CONCLUSION: The obstetric advantages of delivery in the vertical position, compared to the lithotomy position, are: Reduction in the duration of the second stage of labor, less pain, better progress in the second stage of labor and reduction of the operative delivery and assisted delivery; and, the perineal advantages, are: Decrease in perineal tears, less use of episiotomies, higher rates of intact perineum. RECOMMENDATION: Begin to instruct pregnant women about the different vertical positions that you can use at the time of the birth of your child, giving priority to the position you choose to have your baby
INTRODUCCIÓN: Desde la antigüedad, para el nacimiento de sus hijos, las mujeres adoptaban posiciones de tipo vertical que fueron prevaleciendo durante mucho tiempo. Las posiciones verticales benefician a las mujeres en trabajo de parto, al permitir el pujo espontaneo con contracciones más eficientes. OBJETIVO: Determinar las ventajas obstétricas y perineales del parto vertical versus el parto supino. METODOLOGIA: Se realizó la revisión de literatura científica, sobre la ventaja del parto vertical sobre el parto horizontal, en bases de datos como: EBSCO, SCIELO, PUBMED, desde Agosto 2015 hasta la actualidad. DESARROLLO: En la revisión sistemática y meta-análisis realizada por Zang et al, se concluyó que la posición erguida puede reducir la incidencia de parto quirúrgico, parto vaginal instrumental, cesárea, episiotomía, traumatismo perineal severo, dolor severo y acorta la duración de la fase de pujo activo en la segunda etapa del parto. CONCLUSIÓN: Las ventajas obstétricas que presenta el parto en posición vertical, frente a la posición de litotomía, son: Disminución del tiempo de duración de la segunda etapa del parto, menor dolor, mejor progreso en la segunda etapa del trabajo del parto y reducción del parto operatorio y del parto asistido; y, las ventajas perineales, son: Disminución de los desgarros perineales, menor uso de episiotomías, tasas más altas de periné intacto. RECOMENDACIÓN: Comenzar a instruir a las mujeres gestantes sobre las diferentes posiciones verticales que puede usar en el momento del nacimiento de su hijo, dando a la vez, prioridad a la posición que ella elija para tener a su bebé.
Keywords: PARTO VERTICAL; POSICION ERGUIDA; PARTO HORIZONTAL; LITOTOMIA